The Dog Goes to Tend the Herd… On Contextualization of the Estonian Child-Lore Collections - Saarlo, Liina (Tautosakos darbai, 2020)
The paper contextualizes the large and “thick” corpus of children’s songs at the Estonian Folklore Archives, presenting circumstances and prerequisites of its formation. The showcase is the child-lore corpus of Laiuse parish and Priidu Tammepuu, the key figure in its formation.The paper discusses the motives of an amateur folklore collector, conflicts between the contributor and the archival institution. Also, problems of collection by pupils are brought forward, revealing the reasons of marginalisation and dismission of some of the corpus’s content by folklorists, researchers and publishers. Finally, perspectives and possibilities for use of such archival materials are discussed.
Keywords: Estonian Folklore Archives; folklore collection campaigns; child-lore; contributor; literary influences on oral traditions